Analisis Yuridis mengenai Aspek Perlindungan Konsumen yang Berkeadilan dalam Studi Kasus Wanprestasi terhadap Developer dalam Kasus Jual Beli Properti - Arrasyid, Muhammad Zaidan; Utama, Erry Praditya (PT Elaborium Elevasi Indonesia, 2025)
This research focuses on discussing the phenomenon that occurs in the rise of cases of default by property developers regarding property buying and selling transactions. This case raises various legal and social problems for people in Indonesia, including having a detrimental impact on buyers or consumers. That the case of Default by the Developer is based on the Developer's incompetence, such as the Developer's inability or failure to fulfill its promises or obligations in completing the housing project, the quality of the building, or the legality of the land/there is a land dispute between the developer and another party. The normative juridical method with a descriptive analytical approach results in the conclusion that consumer protection regulations and sanctions for default have been established, but the consumer protection aspect has not met justice for consumers, therefore it is recommended to apply appropriate sanctions, reimbursement of all costs, increase supervision of developers, and increase the role BPSK.